Religious Morality in Economic Behavior of Grocers In Sekaran, Semarang - Luthfi, Asma (Universitas Negeri Semarang, 2020)
Economic activity is the main activity carried out by human which its development can be affected by several factors. One of the factors is religion and belief that they have. Religion and economic are two influential elements because religion is able to push the mentality and motivation of human economy. Vice versa, the economy can be a driving force for improving the quality of a person's religious behavior. For the grocers in Sekaran Village, the economic activity that they do is not free from the influence of their religion and belief. The method used in this study was a qualitative method based on descriptive analysis which was located in Sekaran Village, Gunung Pati District, Semarang. This study shows that the economic behavior in the grocery grocer is strongly influenced by their religious spirituality. This can be seen in their view of property as a treasure given by God and should be used to help for fellow human beings, their view on working is based on the God's commands, as well as work ethic that is constituted by the teachings of their religion. This view then affects the entrepreneurial ethics and their economic action which are oriented to religious values.